2021
DOI: 10.1021/acsestwater.0c00240
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical, and Microbiological Water Quality Variation between City and Building and within Multistory Building

Abstract: Municipal drinking water entering buildings can experience degraded water quality due to in-building water treatment devices, plumbing design, materials, and occupancy patterns. To understand water quality patterns, we installed online sensors and collected grab samples throughout a multistory university building to quantify temporal and spatial fluctuations in temperature, pH, free chlorine, dissolved copper, trihalomethanes (THMs), cellular adenosine triphosphate (cATP), and organic matter surrogate (UV254).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Building AZ-1 (Legiolert positivity: 100% [n=7 of 7]; qPCR positivity: 100% [n=7 of 7]) is a green building (LEED-certified); LEED-certified buildings have previously been linked to high water residence times and, in certain cases, L. pneumophila occurrence. 12,65,66 In addition, AZ-1 uses whole-building water softening upon entry of water into the building. A sample collected from a water storage tank immediately after the water softener was positive for L. pneumophila by both Legiolert (10,616 MPN/L) and qPCR (650 gc/L) and had a low chlorine residual (0.05 mg/L as Cl 2 ), indicating that residual disinfectant loss was occurring in the water softener.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Building AZ-1 (Legiolert positivity: 100% [n=7 of 7]; qPCR positivity: 100% [n=7 of 7]) is a green building (LEED-certified); LEED-certified buildings have previously been linked to high water residence times and, in certain cases, L. pneumophila occurrence. 12,65,66 In addition, AZ-1 uses whole-building water softening upon entry of water into the building. A sample collected from a water storage tank immediately after the water softener was positive for L. pneumophila by both Legiolert (10,616 MPN/L) and qPCR (650 gc/L) and had a low chlorine residual (0.05 mg/L as Cl 2 ), indicating that residual disinfectant loss was occurring in the water softener.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations in this building found that the softener was oversized for the building water demand, leading to high water residence time in the softener. 65,66 Building PA-1 (Legiolert positivity: 94% [n=17 of 18]; ddPCR positivity: 67% [n=12 of 18]) is a laboratory-scale experimental shower rig consisting of three water heaters, each of which supplies three showers. The water heaters were operated at 49°C and thermostatic mixing valves limited water temperature to 40°C at the fixtures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have also shown that disinfectant decay in pipe is unavoidable save for glass pipes which is not a suitable premise plumbing material (Nguyen et al, 2012 ; Tolofari et al, 2020 ; Zhang et al, 2017 ). Studies have also shown an increase in THM formation in buildings due to stagnation (Dion‐Fortier et al, 2009 ; Salehi et al, 2020 ) or equipment such as hot water tanks (Dion‐Fortier et al, 2009 ) and water softeners (Richard et al, 2021 ). Leaching of copper into water is undesirable as high levels of copper during short‐term exposure can cause stomach issues while long‐term exposure can cause neurological issues and liver and kidney damage (U.S. Environmental Protection Agency, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…The biofilm of premise plumbing materials has been shown to be a reservoir for L. pneumophila and Pseudomonas aeruginosa , two common OPPPs (Moritz et al, 2010 ). And building equipment, such as water softeners (Richard et al, 2021 ) and hot water tanks (Rhoads et al, 2015 ) can also promote microorganism growth. Lautenschlager et al ( 2010 ) and Bédard et al ( 2018 ) were able to demonstrate that flushing showed a decrease in viable cell count for cold water after varying stagnation events (1 h to 10 days) (Bédard et al, 2018 ; Lautenschlager et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%